Peningkatan Overall Equipment Effectiveness (OEE) Mesin Produksi Section Machining Crankcase R/L Dengan Metode Total Preventif Maintenance (TPM) Dan Implementasi 5S Di PT. AHM - Sudarmono, Sudarmono; Hidayat, Ade Nurul; Prasetya, Dwi Indra; Syahrir, Azhar (JURNAL TEKNIK INDUSTRI, 2023)
Globalization has resulted in increasingly intense competition in the industrial world, especially in the automotive manufacturing industry. This is what drives companies to increase effectiveness and efficiency in each division of their company to increase the quantity and quality of their products so they can compete globally, For fine boring machines by 43% and drilling machines by 44% so that an OEE value of 43.11% is obtained, so the author aims to improve this percentage by implementing Total Productive Maintenance (TPM) maintenance and implementing 5s, After repairing the system using the method TPM and the application of 5s in the machining section. Significant results were obtained from the original OEE value in the period January-May 2022 of 43.11% which could be increased in June - October 2022 with details of tapping machines at85%, drilling machines at85%, and fine machines boring at 85% so that the OEE value is 85%.